Neotropical mammals in natural history collections and research in Rome, Italy - Gippoliti, Spartaco; Castiglia, Riccardo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The occurrence and the history of Neotropical mammal specimens in the collections of naturalistic museums in Rome, Italy, and their scientific utilization is here reviewed. These specimens belong to several scientific expeditions made after the discovery of the new Continent. The oldest specimens date back to the famous Museum of Athanasius Kircher at the Collegio Romano (1651) and to the Museo Zoologico della Università di Roma that was established inside the University of the Pontificial State (Archigymnasium) (1823). Many of these early specimens are now lost due to the complex history of Roman scientific museology, but some specimens are now available mainly in two institutions, the Museo Civico di Zoologia (established in 1932) and the Museo di Anatomia Comparata “Battista Grassi” of “Sapienza” University of Rome (1935). Among the numerous specimens, is noteworthy the presence of a hairy long-nosed armadillo, Dasypus pilosus, the first record in an Italian zoological collection and the 26th known specimen of this species in world museums. More recently, some Roman researchers have maintained a scientific interest for Neotropical mammals, including primates, with collaboration with South American mammalogists. A greater historical knowledge of scientific activities concerning the work of Italians researchers on Neotropical biodiversity should be pursued.
Keywords: Dasypus pilosus; Mammalogy; Naturalistic museum